Non chiedetemi chi sono: il chiasmo del soggetto tra Jacques Lacan e Michel Foucault - Guadagni, Giulia; De Gaetano, Roberto; Cimatti, Felice (My University, 2019)
This dissertation is about the roles played by Jacques Lacan and Michel Foucault in the philosophical debate about the issue of the subject, which involved many philosophers in the Twentieth century. The first chapter opens on the earlier articles that Foucault wrote on psychology and psychoanalysis. Then, I resume the main elements of the Lacanian theory of language. The next two paragraphs focus on two elements that they have in common: anti-naturalism and anti-psychologism. The second part of the chapter is directly dedicated to the issue of the subject. Firstly, I consider Foucault’s statements about that, then I specify which “subject” is the one involved in the “question”, and finally I concentrate on the structuralist operation on the philosophical concept of foundation. Then, I expose in detail the Foucauldian and Lacanian thesis about the subject. It is the first part of the chiasmus: both authors aimed to avoid the reference to transcendental subject and to the identity of consciousness, but while Lacan maintained a subverted subject in his psychoanalytical theory, Foucault didn’t. In the second chapter I analyze some of the occasions of direct debate between them. Firstly, I show how Lacan put his theory in opposition to philosophy, accusing philosophers of a general idealism (including Foucault, as it emerges in the Lacanian lessons about Las Meninas). Then I make a comparison between Lacanian realism of the structure and Foucauldian methodological nominalism. I argue that we cannot understand them without referring to their common refusal of considering language as a system of nomenclature. Only from this Saussurian perspective it is possible to understand the status of reality of the signifiers and of the discursive practices. The last chapter goes back to the question of the subject. In the first paragraph I consider the Foucauldian thesis according to which truth is always a system of obligations, and I expose its consequences. Then, I highlight the equivalence between the Lacanian formulas “I, truth, speak” and “There is no metalanguage”. Considering language as a cut and a cancer, Lacan found himself closed in a trap determined by the limits of language itself. I suggest that is possible to find something similar in Foucauldian work: we cannot live outside any regime of truth. But Foucauldian position is different because he does not consider this ineluctability as a trap. From this difference on, their theoretical strategies diverge. Lacan makes the hypothesis of an impossible real that coincides with the very limits of language and identifies the end of the analysis with a paradoxical failure of the analysis itself. In his researches on subjectivation, Foucault remains in the field of what is possible. If we could have thought that the chiasmus would end with an elimination of the subject in Lacanian theory of the Real, and with a “return” of the subjects in Foucauldian last researches, it appears not to be the case. The chiasmus ends with an opposition between Lacanian Sinthome as an assumption of impossibility and the Foucauldian processes of subjectivation, as a never-ending field of possibility for new inventions.
Dottorato di ricerca internazionale in studi umanistici: Testi, saperi, pratiche dall’antichità classica alla contemporaneità, Ciclo XXXI, a.a. 2018-2019
Keywords: Foucault, Michel; Lacan, Jacques